Metodologia multi-critério para análise da qualidade acústica em igrejas - António P. O. de Carvalho (2008)
The purpose of this research is to develop an algorithm that can translate the acoustic feeling transmitted to the receptor and that is able to quantify the global Acoustic Quality of a Church in a single index using either acoustic or architectural parameters. In order to quantify the Church Acoustic Quality index (QAI), subjective acoustic parameters were used so that the receptors perception of the acoustic behavior can be adequately translated. Using a multi-criteria method, and data from a sample of 13 churches, subjective acoustic parameters were associated with weight factors, whose values were calculated according to the relevance of each parameter in the acoustic behavior of the church. Prediction models were established to calculate the subjective acoustic parameters, using either objective acoustic parameters or architectural parameters.